Interest and non-interest terms in the process of mortgage market clearing: a reply - Browne, F. X.; Thom, Rodney (Economic & Social Studies, 1990)
Thom (1990) argues that, in a situation of excess mortgage demand, loan applicants "with relatively low LV ratios (high DR ratios) have their demands satisfied while those with relatively high LV ratios are placed in a 'mortgage queue'. Hence successful applicants are on their desired demand curves but the aggregate demand curve does not shift and excess demand remains a feature of the market" (my italics). The key to Thom's argument is that, in the circumstances indicated, the aggregate demand curve does not shift. This, however, is no more than a mere hypothesis which does not, I think, possess much apriori appeal. If, after searching the market, an applicant finds that, because of generalised excess demand, there still remains a large discrepancy between what he/she can afford or is willing to pay (including all non-price terms of which the DR is one) and what is required by the building society, that person will clearly cease to actively search for a mortgage. Just like the discouraged job seeker will leave the labour market, the discouraged "mortgage seeker" will leave the mortgage market.
Keywords: Interest rates; Mortgage market; Ireland; Mortgages